Beauty and the beast Reading with Phonics - Greening ;Rosie (China Make Believe Ideas, 2017)
Introducing ten new phonic fairy-tale books designed to develop the reading confidence of young children. The books are aimed at children who can read a little, but who need lively but structured books to help them develop their skills further, focusing particularly on phonics. Using a familiar tale, the entertaining, rhyming text complements the child's more formal learning. A page at the beginning of each book helps adults to understand how best to use the book with the child. At the end of each book, there are fun activities to reinforce the key phonic sounds from the book. Clare Fennel's charming illustrations will engage and entertain children as they read